2022
DOI: 10.1038/s41598-022-19542-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic back pain sub-grouped via psychosocial, brain and physical factors using machine learning

Abstract: Chronic back pain (CBP) is heterogenous and identifying sub-groups could improve clinical decision making. Machine learning can build upon prior sub-grouping approaches by using a data-driven approach to overcome clinician subjectivity, however, only binary classification of pain versus no-pain has been attempted to date. In our cross-sectional study, age- and sex-matched participants with CBP (n = 4156) and pain-free controls (n = 14,927) from the UkBioBank were included. We included variables of body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Tagliaferri et all. (25) used a univariate approach for initial variable selection before clustering cLBP patients. This has the risk of discarding variables from the analysis that are informative for clustering when combined with other variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tagliaferri et all. (25) used a univariate approach for initial variable selection before clustering cLBP patients. This has the risk of discarding variables from the analysis that are informative for clustering when combined with other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Tagliaferri et all. (25) found 5 subgroups of cLBP patients, mostly divided with reference to depressive symptoms and social isolation. Our data did not contain detailed measurements of psychosocial factors, which could have limited partitioning subgroups into further clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3T MRI scanner with a 32 channel receive-only phased-array head coil will be used. As in preliminary work [ 31 , 47 ], high resolution magnetisation prepared rapid acquisition gradient echo (MP2RAGE) T1-weighted structural data will be acquired to assess grey matter volumes. Resting state functional connectivity in pain networks will be assessed using an EPI sequence and those data will be pre-processed, denoised and analysed using standardized pipelines.…”
Section: Methodsmentioning
confidence: 99%
“…There is an evidence gap for a study to use data-science techniques in LBP in an appropriate sample size. Since this review, work from our group [ 31 ], using data from the UK Biobank, showed that sub-groups could be derived in (chronic) LBP on the basis of psychosocial variables and then accurately classified, but the data set lacked spinal tissue and pain sensitisation measures and key clinical data (e.g. pain intensity, disability and pain duration).…”
Section: Introductionmentioning
confidence: 99%